15.8k views
3 votes
Simplify -2[9 - (x + 7)]

2 Answers

3 votes

Answer:

-4x+2

Explanation:

User Ash Singh
by
5.1k points
5 votes
Hey there!
-2[9 - (x + 7)] \\ \\ \\( -2(9) + -2(-x) + -7) \\ \\ -2(9) +-2(-x) + -2 (-7) \\ \\ \\ -2(9) = -18 \\-2(-x) = 2x \\ -2(-7) = 14 \\ \\ \\ -18 + 2x + 14 \\ \\ \\ \\ Combine \\ like\\ terms: -18 , 14 \\ \\ \\ -18 +14 = -4 \\ \\ \\ \\ Answer: 2x - 4 \\ \\ \\ \\ \\ \\ Good\\ luck \\ on \\ your \\ assignment \\ and \\ enjoy \\ your \\ day!

~
LoveYourselfFirst:)
User Pln
by
5.3k points